2011 International Conference on Computer Vision 2011
DOI: 10.1109/iccv.2011.6126529
|View full text |Cite
|
Sign up to set email alerts
|

Multiview structure from motion in trajectory space

Abstract: Most nonrigid objects exhibit temporal regularities in their deformations. Recently it was proposed that these regularities can be parameterized by assuming that the nonrigid structure lies in a small dimensional trajectory space. In this paper, we propose a factorization approach for 3D reconstruction from multiple static cameras under the compact trajectory subspace representation. Proposed factorization is analogous to rank-3 factorization of rigid structure from motion problem, in transformed space. The be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 23 publications
2
15
0
1
Order By: Relevance
“…These additional constraints above were called basis constraints [30][31][32][33][34]. They removed the inherent basis ambiguity by doing this.…”
Section: Shape Basismentioning
confidence: 99%
See 1 more Smart Citation
“…These additional constraints above were called basis constraints [30][31][32][33][34]. They removed the inherent basis ambiguity by doing this.…”
Section: Shape Basismentioning
confidence: 99%
“…A large number of efforts had been made for it, and the result is delightful. For example, Aamer Zaheer et al [34] made a big contribution to provide algorithms for recovering the non-rigid structure from motion well with missing data by using DCT as well as Principle Component Analysis (PCA) basis. A large number of experiments showed that trajectory had obvious advantages in handling with occlusion data for the smoothness property of curves.…”
Section: Trajectory Basismentioning
confidence: 99%
“…Temel bileşen vektörleri elde edildikten sonra her bir çerçeve için öznitelik vektörlerinin hesaplanma aşamasına (5) geçiliyor. Bu aşamada çerçeve içinde boş değer ile karşılaştığımızda ise bu değere sahip işaretçi( kolonu) çıkartılıyor ve temel bileşen vektörlerinde o işaretçiye karşılık gelen kısım( satırı) da çıkartılarak öznitelik vektör değerlerinin hala hesaplanabilir durumda kalması sağlanıyor [17]. Bu sayede verideki yerel kayıplar TBA uygulanırken telafi edilmiş oluyor.…”
Section: Deneylerunclassified
“…The methods addressing this problem can be divided into three categories: imputation, alternation and non-linear optimisation. Imputation algorithms attempt to fill in the missing data entries using complete subset of the data [18,22]. These methods are simple but cannot handle real data, which often tend to be very noisy.…”
Section: Introductionmentioning
confidence: 99%